Alternative Payment Models in Total Joint Arthroplasty Under the Affordable Care Act. Issue 3 (March 2019) - Cizmic, Zlatan; Novikov, David; Feng, James; Iorio, Richard; Meftah, Morteza
Abstract : Since the passage of the U.S. Patient Protection and Affordable Care Act (ACA), health care has transitioned from a volume-based enterprise to a quality-based enterprise. Under this legislation, Alternative Payment Models (Bundled Payments for Care Improvement [BPCI], Comprehensive Care for Joint Replacement [CJR], and Accountable Care Organizations [ACOs]) have been developed to provide stakeholders with reimbursement systems that reward high-quality care and cost reduction. The goal of this article was to elaborate on the various Alternative Payment Models and recent amendments and how these unique payment paradigms may offer orthopaedic surgeons innovative principles to further advance the quality and efficiency of total joint arthroplasty.